2003
DOI: 10.1016/s0095-0696(02)00020-7
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative and non-cooperative harvesting in a stochastic sequential fishery

Abstract: \W_e examine cooperative harvesting in a sequential fishery with stochastic shocks in recruitment. Two fleets harvest in a stochastic interception fishery. We analyze cooperative management as a non-cooperat ive game, where deviations from cooperative harvesting are deterred by the threat of harvesting at non-coopera tive levels for a fixed number of periods whenever the initial stock falls below a trigger level. We illustrate the sequential harvesting game with an application to the Northern Baltic salmon fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Australia and Papua New Guinea have 20+ years of cooperation in managing the Torres Strait rock lobster fishery and there are mutual benefits for continuous cooperation. Munro (1979) and Laukkanen (2003) have provided solid analyses based on game theory and concluded that cooperative harvesting yields participants substantial gains in terms of expected pay-offs. This study provides further quantitative evidence that Australia and Papua New Guinea should use cooperative harvest strategies for the benefit of both countries and for the long-term sustainability of the Torres Strait rock lobster fishery.…”
Section: Discussionmentioning
confidence: 99%
“…Australia and Papua New Guinea have 20+ years of cooperation in managing the Torres Strait rock lobster fishery and there are mutual benefits for continuous cooperation. Munro (1979) and Laukkanen (2003) have provided solid analyses based on game theory and concluded that cooperative harvesting yields participants substantial gains in terms of expected pay-offs. This study provides further quantitative evidence that Australia and Papua New Guinea should use cooperative harvest strategies for the benefit of both countries and for the long-term sustainability of the Torres Strait rock lobster fishery.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a host of researchers have refined these insights. There have been attempts to model common-pool resources as dynamic games, with various assumptions about discounting, and payoffs either independent of resource stock (Benhabib and Radner, 1992;Cave, 1987;Dutta, 1995) or dependent on stock (Hannesson, 1997;Laukkanen, 2003;Tarui et al, 2008). These models have also introduced a range of assumptions about monitoring, from perfect monitoring and individual sanction (Casari and Plott, 2003;Ostrom, 1990) to imperfect monitoring and unobservable individual actions (Cason and Khan, 1999;Chermak and Krause, 2002;Isaac and Walker, 1988).…”
Section: The Tragedy Of the Commonsmentioning
confidence: 99%
“…Laukkanen (2003) considers stochastic stock recruitment in a transboundary fishery where two fleets operate sequentially, and describes a self-enforcing agreement that can support cooperative harvesting. Another important source of variation is the ability of management in each country participating in negotiations to achieve management targets in any one year.…”
Section: Introductionmentioning
confidence: 99%
“…We compare the implications of implementation uncertainty and recruitment uncertainty for cooperative harvesting. Differing from the sequential fishery model in Laukkanen (2003), we consider a shared fishery where the competing countries harvest simultaneously. Growth and reproduction depend on how much each fleet leaves behind after harvesting.…”
Section: Introductionmentioning
confidence: 99%